The Quality and helpfulness of answers to eating disorder questions in yahoo! answers: Teens speak out. Issue 1 (2015) - Bowler, Leanne; Monahan, Jocelyn; Jeng, Wei; Oh, Jung Sun; He, Daqing
ABSTRACT: This research project investigated teens' perspectives on the quality and helpfulness of health information about eating disorders found on Yahoo! Answers, a Social Q&A site. A mixed methods approach was applied, using survey methods and semi‐structured group interviews to gather data for the project. Eighteen teens completed a web‐based questionnaire using sample question/answer sets about eating disorders from Yahoo! Answers . The teen participants were asked to choose one answer as "best" and then rank its credibility, accuracy, reliability, and helpfulness. Open‐ended questions allowed teens to explain the rationale for their choice of "best" answer and to discuss why the chosen answer might (or might not) be helpful for teens. Following the questionnaire, six teens participated in a focus group interview using a semi‐structured format that asked open‐ended "why" questions in order to draw forth comments on criteria for evaluating the quality and and helpfulness of health information in Yahoo! Answers, as well as to reveal aspects of critical thinking. Findings suggest that, 1) teens make a distinction between health information in Social Q&A that is credible versus that which is helpful, 2) they value health information that isn't from a credible source if it addresses other needs, and, 3) when making judgments about health information on the Web, they apply an array of heuristics related to information quality, opinion, communication style, emotional support and encouragement, guidance, personal experience, and professional expertise .